Autonomic Cross-Innervation in Patients With Neurofibromatosis Type 2: Frey Syndrome and Unilateral Epiphora With Rhinorrhea. (6th August 2019) - Evans, Erica; Nascene, David; Sommer, Katherine; Moertel, Christopher
The authors present 2 cases of cross-innervation in patients with neurofibromatosis type 2. In the first case, an iodine test was performed to demonstrate Frey syndrome in a 28-year-old female with neurofibromatosis type 2 who developed symptoms at age 10 years. The second patient is an 18-year-old female with neurofibromatosis type 2, 2 years status post left vestibular schwannoma subtotal resection who presented with paradoxical unilateral lacrimation and rhinorrhea triggered by heat stress and exercise. The pathophysiology of these cases is discussed.